URGENSI SARANA DAN PRASARANA SEKOLAH TERHADAP AKTIVITAS EKSTRAKURIKULER SISWA SEKOLAH DASAR - Arfi Purnama Nur Indah; Irawati Nuraeni; Nurina Asri Fitriani; Selvi Novitasari; Agus Mulyana (STKIP Subang, 2023)
Education is an important thing in human life. Therefore, in providing education, there needs to be support from various parties. Support for the provision of education is not only from the government, teachers, or parents but also from the existence of supporting facilities and infrastructure, which also includes support for the provision of much higher-quality education. The existence of supporting school facilities and infrastructure not only has an impact on student learning activities but also on the extracurricular activities that students participate in. Extracurricular activities are a form of activity that provides a forum for students to improve their abilities outside of academics. Extracurricular activities require complete and good facilities and infrastructure in order to achieve effectiveness in their implementation. In reality, on the ground, there are still limitations in the provision of facilities and infrastructure in schools. This research aims to determine the importance of school facilities and infrastructure for elementary school students' extracurricular activities. This research uses descriptive research with a qualitative approach. This research data was collected through interviews and observations. The results of this research show that facilities and infrastructure are important because they are related to the purpose of extracurricular activities which can increase and develop students' potential, shape students' social skills, serve as recreational activities for students, and have the potential for career planning for students.